KEBIJAKAN ELECTRONIC GOVERNMENT DALAM MENINGKATKAN PENYELENGGARAAN PELAYANAN PUBLIK - Hamdi, Alhilal; Abdi, Abdi; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research shows that the electronic government policy in administering public services for the Enrekang Regency population and civil registration service as seen from the following aspects: 1) Communication, in the administration of public services for the Enrekang Regency population and civil registration service, is in accordance with existing policies where the communication carried out is very important as the nature of transparency to the community. 2) resources, in providing public services for the Enrekang Regency population and civil registration service, are good with development and training provided so as to improve their performance. 3) Disposition, in providing public services for the Regency population and civil registration service. is quite good in terms of attitude and responsibilities. 4) the bureaucratic structure, in providing public services for the Regency's population and civil registration services, is good enough as a source of information for leaders or executives in producing various policies.